Article processing charges suppress the scholarship of doctoral students - Joshua Wang (European Science Editing)
The open access movement has drastically reconfigured the financial burdens of scholarly publishing. Yet, the influence of a marketized scholarly publishing system on doctoral education remains unexplored. I reflect on my own PhD candidature to illustrate how article processing charges disempower doctoral candidates. I argue that the current open access publishing model unfairly advantages candidates with personal, familial and/or institutional wealth. The inequalities imposed on doctoral students by our sectors’ current publishing habits ultimately bias who will be paid to produce and safeguard knowledge in the future. Doctoral students can no longer be ignored in debates over open access publishing.